Early traumatic life events, parental attitudes, family history, and birth risk factors in patients with depressive disorder and healthy controls. (February 2013) - Bandelow, Borwin; Gutermann, Julia; Peter, Helmut; Wedekind, Dirk
Abstract Objective. Only few studies have compared the frequency of traumatic life events during childhood in inpatients with depression with a healthy control group. Methods. Consecutively admitted inpatients with depression (n = 79), most of whom belonged to the melancholic subtype (n = 73; 92.4%), and healthy controls (n = 110) were investigated using a comprehensive retrospective interview with 203 questions regarding childhood traumatic life events, parental attitudes, family history of psychiatric disorders and birth risk factors. Results. Depressed patients had significantly more severe traumatic events (mean score 1.33; SD 1.4) than control subjects (0.85; SD 1.2) on a 0–10 point "severe trauma scale". 70.9% (n = 56) of the depressed patients, but only 48.2% (n = 53) of the controls reported at least one severe traumatic event. When looking at single events, only few differences were found between patients and controls. Compared to controls, patients described significantly higher rates of psychiatric disorders in their families, in particular depression. Parental rearing styles were rated as more unfavorable in the patient group. In a logistic regression model, of all possible etiological factors examined, only a family history of psychiatric disorders showed a significant influence (OR = 3.6). Conclusions. Melancholic depression seems to be less associated with traumatic events than other psychiatric disorders.